PERANAN EKSPOR-IMPOR TERHADAP PEREKONOMIAN JAWA TIMUR DENGAN PEMBENAHAN FUNGSI PELABUHAN DI JAWA TIMUR - Soegiri, Harry (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2008)
The negative impact of global financial crisis to the economi growth of east java is imployment added. Existing condition of eksport import in east java is positive growth, but the challege of the effect lapindo and the port of Tanjung Perak is overload. See the problem overall to impact of economic growth of east java, the solution is use of optimalization the port of Tanjung Wangi Banyuwangi. Keyword:        Global Financial Crisis, Lapindo, Economic Growth, Port Tanjung Wangi.